«НОВА ВІЗУАЛЬНІСТЬ», ОБРАЗ І УЯВА В КОНТЕКСТІ NEW MEDIA ART. - Барінова, Яна (Doxa / Doksa, 2023)
The publication examines the specifics of the image, imagination and the formation of "new visuality" in the context of the development of New Media Art. The analysis of the problem is carried out on two levels: a) conceptual searches of theorists of media philosophy, who proclaimed an iconic turn in modern culture and art; b) art projects of modern artists working in the field of new media art (technoart, bioart, software art, etc.). Modern philosophy in the light of new trends and socio-cultural practices understands the problems of correspondence between the image and the original, representation, the crisis of the concept of Image in modern art. It is about the formation of a new media narrative, which is capable of exploring new compositional possibilities offered, for example, by a computer database. The basic principles of new media are outlined: modularity, automation, variability, transcoding, etc.